Let Heritage Die! The Ruins of Trams at Depot No. 5 in Wroc?aw, Poland - Kobiałka, Dawid (Journal of Contemporary Archaeology, 2015)
This paper is a case study of the trams now kept at Depot No. 5 at Legnicka 65 in Wroc?aw, Poland. The site provides a context for exploring two core issues around archaeological approaches to the contemporary past. The first is how materiality and immateriality are deeply interwoven in the context of modern heritage sites, with the overlap providing the grounds for discussion on the material theology of modern ruins. The second is the consequences of seeing modern ruins as heritage sites worth preserving for future generations. The conclusion of this paper is that if heritage is to be saved, it should be saved first of all from its saviours.